Ethnography and Management Talent as a Tools to Knowledge Sharing in the Consulting Sector - Costa, Renato Lopes da; GonÃ§alves, Rui; AntÃ³nio, Nelson; Pereira, Leandro; Dia, Pedro (Journal of Reviews on Global Economics, 2019)
The goal of this paper was to understand if the current KM practices in a consultancy organization met what the workers preferred and in what way ethnography could be integrated in these practices and give guidelines for future studies where it can be integrated in the talent management process. The results showed an organization with employees willing to share their knowledge and obtain it through methods that involve the participative observation employed in ethnography as in the Socialization process of the SECI Model.